Megalencephaly and Macrocephaly - Winden, Kellen D.; Yuskaitis, Christopher J.; Poduri, Annapurna (Seminars in Neurology, 2015)
Megalencephaly is a developmental disorder characterized by brain overgrowth secondary to increased size and/or numbers of neurons and glia. These disorders can be divided into metabolic and developmental categories based on their molecular etiologies. Metabolic megalencephalies are mostly caused by genetic defects in cellular metabolism, whereas developmental megalencephalies have recently been shown to be caused by alterations in signaling pathways that regulate neuronal replication, growth, and migration. These disorders often lead to epilepsy, developmental disabilities, and behavioral problems; specific disorders have associations with overgrowth or abnormalities in other tissues. The molecular underpinnings of many of these disorders are now understood, providing insight into how dysregulation of critical pathways leads to disease. The advances in molecular understanding are leading to improved diagnosis of these conditions, as well as providing new avenues for therapeutic interventions.
Keywords: megalencephaly; hemimegalencephaly; macrocephaly; somatic mutation